Joint User Clustering and Beamforming in Non-Orthogonal Multiple Access Networks - Ha-Ryung Kim; Jiasi Chen; Jongwon Yoon (IEEE Access, 2020)
The demand for higher data rate in wireless networks continues to grow, however the wireless spectrum cannot meet ever-increasing demands. Non-orthogonal Multiple Access (NOMA) technology is attracting attentions to overcome the lack of resource spectrum and increase spatial reuse. Traditionally, data is delivered in an orthogonal fashion in the frequency or time domain, whereas NOMA leverages power domain to improve spectral reuse. User clustering is one of the key features that significantly affects NOMA's throughput performance and fairness among the users in the network. In addition to NOMA, beamforming increases spectral efficiency by improving SNR for specific users (and groups) and reducing interference across the clusters. However, combining beamforming with NOMA is a challenging and complex problem because beamforming for improving the reuse of spectral resources is tightly coupled with user clustering in NOMA. In this paper, we introduce a joint user clustering and beamforming scheme that maximizes the network throughput in NOMA with beamforming. Toward this goal, we carefully analyze several features that significantly affect the system throughput and design a heuristic algorithm based on the inferences. Our algorithm increase the signal power in NOMA and effectively reduce both beamforming and NOMA interference. Evaluation results reveal that our solution provide higher utility (sum rate) than other existing schemes and significantly improve fairness among users regardless of the channel conditions.